UNHCR and Current Challenges in International Refugee Protection - Kelley, Ninette; Durieux, Jean-Francois (Refuge: Canada’s Journal on Refugees, 2004)
The international refugee protection regime has had both a successful and a troubled history. It has succeeded in providing international protection to millions of refugees when their own States have been unable or unwilling to do so. Despite this considerable achievement, the regime has at times failed to solve serious refugee protection problems and has not been able to effect durable solutions for many of the world’s refugees. This essay examines the current challenges to the regime from the perspectives of those most affected by them, recognizing that many of these challenges are not new. It examines how UNHCR’s mandate and activities have expanded to meet the larger number and diverse needs of those under its care. As well, it reviews the recent initiatives launched by UNHCR to strengthen international protection for refugees and expand the availability of durable solutions through enhanced multilateral cooperation.